The Kalman filter on stochastic time scales. (August 2019) - Poulsen, Dylan; Wintz, Nick
Abstract: In this paper, we discretize a stochastic linear time-invariant system to a dynamic system on a time scale. We then develop a Kalman filter to estimate the true state for the corresponding system. Here, the measurement-update and time-update equations account for the size of the time step when the time scale is generated randomly. Numerical examples are also provided.